Prevalence And Morphometric Analysis Of Fossa Navicularis Magna In Dry Human Skulls - Maria Tasleem; Mohtasham Hina; Fauzia Qureshi; Imtiaz Aslam; Iram Atta; Raafea Tafweez (Journal of Rawalpindi Medical College, 2023)
Introduction: Basiocciput is the part of occipital bone present on the inferior aspect of skull. Fossa Navicularis Magna-an osseous defect is a variation in normal anatomy of basiocciput. Lately few case reports presented this fossa as a cause of spread of infection from nasopharynx to brain resulting in meningitis and osteomyelitis.